Interest Rate Sensitivity of Spanish Industries: A Quantile Regression Approach. (22nd December 2015) - Ferrando, Laura; Ferrer, Román; Jareño, Francisco
Abstract : This paper examines the degree of interest rate exposure of Spanish industries for the period 1993–2012 using the quantile regression methodology. The empirical results show that the Spanish stock market exhibits a significant level of interest rate sensitivity, although there are notable differences across industries and over time. In addition, the impact of changes in interest rates on industry equity returns tends to be more pronounced in extreme market conditions, i.e. during crises or bubbles in stock markets, than in normal periods. This finding may be related to herding behavior of stock investors during periods of market stress.